Vitamin D and Depression in Women: A Mini-review - Boulkrane, Mohamed S.; Fedotova, Julia; Kolodyaznaya, Valentina; Micale, Vincenzo; Drago, Filippo; van den Tol, Annemieke J. M.; Baranenko, Denis (Current Neuropharmacology, 2020)
Affective-related disorders, including depression, are constantly rising, complicating people’s personal lifestyle increasing disqualification and hospital care. Because of the high intensity of urbanization, our lifestyle and food have altered dramatically in the last twenty years. These food modifications have been associated with scores of depression and other affective-related disorders in urbanized countries with high economic levels. Nutrients imbalance is considered as one of the critical causes enabling the pathophysiological mechanisms for the development of psychiatric disorders. The application of additional nutritional interventions for treatment of mood deteriorations can be beneficial for both the prophylaxis and therapy of affective-related disorders. This paper will review recent research on the relation of Vitamin D levels and the epidemiology of depression in women. In this paper, we will provide an overview of the results of a variety of different studies taking into account research which both suggests and refutes an association. Based on these findings we will propose important directions for future research in relation to this topic.
Keywords: mood